PERENCANAAN DAN ANALISIS KELAYAKAN INVESTASI PROYEK PEMASANGAN KAPASITOR BANK PADA INSTALASI PEMANFAATAN ENERGI LISTRIK - Epiwardi; Ruwahjoto; Heri Sungkowo (Jurnal Teknik Ilmu dan Aplikasi, 2020)
The low power factor in the electricity installation of Sumber Wendit 3 water pumping stations causes a bill of excess reactive energy usage or kVARh, so that the cost of using electricity becomes higher. The excess use of reactive energy can be compensated by additional investment in installing capacitor banks in the main distribution panel (MDP) Sumber Wendit 3 water pump station. Based on the data and problems, it is planned to install capacitor banks that meet the standards with a target of 0.90 and 0.95 lagging. From the results of the planning, we need 150 kVAR and 250 kVAR capacitors, with an investment value of Rp. 94,983,790 and - Rp. 120,781,210. After an investment feasibility test using the Payback Period (PP) method, it is known that for a 150 kVAR bank capacitors, the investment return is technically 2.88 months and economically is 4.01 and 3.17 months. For 250 kVAR bank capacitors, the return on investment is technically 3.66 months and economically 5.1 and 4.03 months. When compared with the economic life of the investment is 10 years, the investment of the bank capacitor installation project is very profitable and feasible to carry out.